Human mesenchymal stem cells modulate inflammatory cytokines after spinal cord injury in rat - Urdzíková, Lucia Machová; Růžička, Jiří; LaBagnara, Michael; Kárová, Kristýna; Kubinová, Šárka; Jiráková, Klára; Murali, Raj; Syková, Eva; Jhanwar-Uniyal, Meena; Jendelová, Pavla (International journal of molecular sciences, 2014)
Transplantation of mesenchymal stem cells (MSC) improves functional recovery in experimental models of spinal cord injury (SCI); however, the mechanisms underlying this effect are not completely understood. We investigated the effect of intrathecal implantation of human MSC on functional recovery, astrogliosis and levels of inflammatory cytokines in rats using balloon-induced spinal cord compression lesions. Transplanted cells did not survive at the lesion site of the spinal cord; however, functional recovery was enhanced in the MSC-treated group as was confirmed by the Basso, Beattie, and Bresnahan (BBB) and the flat beam test. Morphometric analysis showed a significantly higher amount of remaining white matter in the cranial part of the lesioned spinal cords. Immunohistochemical analysis of the lesions indicated the rearrangement of the glial scar in MSC-treated animals. Real-time PCR analysis revealed an increased expression of Irf5, Mrc1, Fgf2, Gap43 and Gfap. Transplantation of MSCs into a lesioned spinal cord reduced TNFα, IL-4, IL-1β, IL-2, IL-6 and IL-12 and increased the levels of MIP-1α and RANTES when compared to saline-treated controls. Intrathecal implantation of MSCs reduces the inflammatory reaction and apoptosis, improves functional recovery and modulates glial scar formation after SCI, regardless of cell survival. Therefore, repeated applications may prolong the beneficial effects induced by MSC application.
Keywords: fibroblastový růstový faktor 2; Receptors, Immunologic; Male; Rats, Wistar; Tumor Necrosis Factor-alpha; Interleukins; interleukiny; interferonové regulační faktory; receptory imunologické; Mesenchymal Stem Cell Transplantation; mužské pohlaví; potkani Wistar; chemokin CCL5; lokomoce; Chemokine CCL5; krysa rodu Rattus; Interferon Regulatory Factors; Animals; Locomotion; lidé; GAP-43 Protein; Spinal Cord Injuries; Humans; poranění míchy; zvířata; gliový fibrilární kyselý protein; Rats; Glial Fibrillary Acidic Protein; protein GAP-43; TNF-alfa; Fibroblast Growth Factor 2; transplantace mezenchymálních kmenových buněk; Mesenchymal Stem Cells; mezenchymální kmenové buňky